Foreign Terrorist Fighters Indonesia: Belief in A Just World and Terrorism - Rahmanto, Didik Novi; Meliala, Adrianus E.; Andi Lolo, Ferdinand (Technium Social Sciences Journal, 2020)
The phenomenon of foreign terrorist fighters’ movement to Syria to join ISIS (Islamic State of Iraq and Syria) has received enormous attention in the world. Tens of thousands of individuals are moving from various parts of the world, including Indonesia, to join the Caliphate that ISIS is fighting for. There are still many reasons for the departure of foreign terrorist fighters to Syria, so this study will examine those that have not been revealed before. This is a qualitative research project using in-depth interviews as data collection techniques. There are 20 speakers who were foreign terrorist fighters but had returned to Indonesia. Just World Theory is used as a framework for thinking in this research. The findings show that not only the issue of religious ideology is the reason for the departure of foreign terrorist fighters to Syria but also the illusion of utopian life they imagined abroad. The findings of this study categorize the respondents' answers in seven ways, i.e. fair and prosperous life, verses and hadith, helping the cause of fellow Muslim who are being wronged, heaven, khilafah, living life like in the age of the prophet, and the order of hijrah.